Knowledge, Attitude and Practice Regarding Menstrual Hygiene Among Girls of Government School - Shahi, Bibhooti; Singh, Shreejana; Joshi, Deepak Raj; Maharjan, Ajanta (Journal of Nepal Paediatric Society, 2022)
Introduction: Menstruation is a natural phenomenon unique to women and menstrual hygiene is fundamental to the wellbeing of women and girls. Menstruation is the process of periodic discharge from the female genital tract due to hormonal influence and takes place within the interval of 28 days. The objective of the study was to find out knowledge, attitude and practice regarding menstrual hygiene among adolescent girls of the Government school. Methods: A descriptive study was carried out among 100 adolescent girls attending selected schools of Birgunj, Nepal using pretested self-administered questionnaires. Proportional Stratified Sampling was used. During data collection privacy and confidentiality was ensured. The data were analyzed using SPSS version 16 through descriptive statistical methods and inferential statistical methods. Results: This study revealed that majority of the girls (32%) have good knowledge, 93% have good attitude and 23% girls have good practice. There was significant association (p < 0.05) between the level of practice and age of menarche but there was no any significant association (p < 0.05) between level of knowledge and attitude with selected variables regarding menstrual hygiene. Conclusions: This study concludes that though the majority of the girls have, good attitude, many have poor knowledge and practice about menstrual hygiene.